Analysis of radiation patterns of rectangular microstrip antennas with uniform substrate - Boualleg, A.; Merabtine, N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Microstrip antennas are useful as antennas mounted on moving vehicles such as cars, planes, rockets, or satellites, because of their small size, light weight and low profile. Since its introduction in 1985, the features offered by this antenna element have proved to be useful in a wide variety of applications, and the versatility and flexibility of the basic design have led to an extensive amount of development and design variations by workers hroughout the world.